Calcolo Scientifico : Esercizi e problemi risolti con MATLAB e Octave /: Esercizi e problemi risolti con MATLAB e Octave. (2017) - Quarteroni, Alfio; Saleri, Fausto; Gervasio, Paola
No abstract available